2018
DOI: 10.1111/mpp.12665
|View full text |Cite
|
Sign up to set email alerts
|

The diguanylate cyclase GcpA inhibits the production of pectate lyases via the H‐NS protein and RsmB regulatory RNA in Dickeya dadantii

Abstract: Dickeya dadantii 3937 secretes pectate lyases (Pels) to degrade plant cell walls. Previously, we have demonstrated that EGcpB and EcpC function as bis-(3',5')-cyclic dimeric guanosine monophosphate (c-di-GMP)-specific phosphodiesterases (PDEs) to positively regulate Pel production. However, the diguanylate cyclase (DGC) responsible for the synthesis of c-di-GMP and the dichotomous regulation of Pel has remained a mystery. Here, we identified GcpA as the dominant DGC to negatively regulate Pel production by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…As, our results (Fig. B and C) showed that Hfq controls T3SS and Pel through additional pathways independent of PecT, and c‐di‐GMP negatively regulates T3SS, Pel and swimming motility in D. dadantii (Yi et al ., ; Yuan et al ., ; Yuan et al ., ), we further assessed whether Hfq controls T3SS and Pel through c‐di‐GMP signalling. We first compared the intracellular c‐di‐GMP levels between wild‐type and Δ hfq using ultra performance liquid chromatography coupled with tandem mass spectrometry (UPLC‐MS–MS).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As, our results (Fig. B and C) showed that Hfq controls T3SS and Pel through additional pathways independent of PecT, and c‐di‐GMP negatively regulates T3SS, Pel and swimming motility in D. dadantii (Yi et al ., ; Yuan et al ., ; Yuan et al ., ), we further assessed whether Hfq controls T3SS and Pel through c‐di‐GMP signalling. We first compared the intracellular c‐di‐GMP levels between wild‐type and Δ hfq using ultra performance liquid chromatography coupled with tandem mass spectrometry (UPLC‐MS–MS).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we explored the contributions of GcpA and GcpL to T3SS and Pel in wild‐type, the hfq mutant, and the hfq / pecT double mutant. Unlike the gcpA deletion that increases both the hrpA expression and Pel production (Yuan et al ., ), deletion of gcpL in the wild‐type background only slightly increased Pel production (Yuan et al ., ) and had no effect on the expression of hrpA (data not shown). Deletion of either of gcpA or gcpL in the hfq mutant background did not alter T3SS or Pel (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations